The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1167/9.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Cross-orientation masking in human color vision

Abstract: Detection of a Gabor pattern is impaired in the presence of a similar pattern of orthogonal orientation, a phenomenon known as cross-orientation masking (XOM). Here we investigate the role of color in cross-orientation masking. We measured contrast detection thresholds to horizontally oriented Gabors overlaid by similar Gabors of a different orientation. Red-green chromatic masking was compared to achromatic masking for a wide range of spatial and temporal frequencies, orientations, and masks contrasts. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 77 publications
4
33
0
Order By: Relevance
“…Here we used only two oriented components, one red-green chromatic and one luminance defined. This was done to avoid possible contamination of the results from low-level masking effects which have been described between luminance and color (e.g., Medina & Mullen, 2009). …”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we used only two oriented components, one red-green chromatic and one luminance defined. This was done to avoid possible contamination of the results from low-level masking effects which have been described between luminance and color (e.g., Medina & Mullen, 2009). …”
Section: Aimmentioning
confidence: 99%
“…In color vision, masking follows a different pattern: Masking appears to be isotropic, i.e., not dependent on mask orientation (Medina & Mullen, 2009). An orthogonally-oriented (also referred to as cross-oriented) stimulus usually shows suppressive effects, but masking can be facilitatory (Meese & Holmes, 2007) at low temporal frequency.…”
Section: Facilitatory and Suppressive Effects Within Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that XOM may be associated with the subcortical, magnocellular pathway or its cortical projections. To test this hypothesis, Medina and Mullen (2009) compared XOM for binocularly presented achromatic and isoluminant red-green stimuli at equivalent spatial and temporal frequencies (0.375-1.5 cpd, 2-8 Hz) and found suppression was significantly greater for the chromatic stimuli. Since red-green stimuli are detected exclusively by the parvocellular pathway of the lateral geniculate nucleus (LGN), this indicates that XOS is as strong in the chromatic parvocellular pathway and its projections as in the magnocellular pathway, and suggests that XOS is not confined to one specific subcortical pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Medina and Mullen (2009) reported that XOM was greater for chromatic than achromatic stimuli at equivalent spatial and temporal frequencies. Here we address whether the greater suppression found in binocular color vision originates from a monocular or interocular site, or both.…”
mentioning
confidence: 98%